Extended pancreatectomy in pancreatic ductal adenocarcinoma: Definition and consensus of the International Study Group for Pancreatic Surgery (ISGPS) - Hartwig, Werner; Büchler, Markus W. (Surgery, 2014)
Background - Complete macroscopic tumor resection is one of the most relevant predictors of long-term survival in pancreatic ductal adenocarcinoma. Because locally advanced pancreatic tumors can involve adjacent organs, “extended” pancreatectomy that includes the resection of additional organs may be needed to achieve this goal. Our aim was to develop a common consistent terminology to be used in centers reporting results of pancreatic resections for cancer. - Methods - An international panel of pancreatic surgeons working in well-known, high-volume centers reviewed the literature on extended pancreatectomies and worked together to establish a consensus on the definition and the role of extended pancreatectomy in pancreatic cancer. - Results - Macroscopic (R1) and microscopic (R0) complete tumor resection can be achieved in patients with locally advanced disease by extended pancreatectomy. Operative time, blood loss, need for blood transfusions, duration of stay in the intensive care unit, and hospital morbidity, and possibly also perioperative mortality are increased with extended resections. Long-term survival is similar compared with standard resections but appears to be better compared with bypass surgery or nonsurgical palliative chemotherapy or chemoradiotherapy. It was not possible to identify any clear prognostic criteria based on the specific additional organ resected. - Conclusion - Despite increased perioperative morbidity, extended pancreatectomy is warranted in locally advanced disease to achieve long-term survival in pancreatic ductal adenocarcinoma if macroscopic clearance can be achieved. Definitions of extended pancreatectomies for locally advanced disease (and not distant metastatic disease) are established that are crucial for comparison of results of future trials across different practices and countries, in particular for those using neoadjuvant therapy.
Gesehen am 24.09.2020